PHASE TRANSITION IN Fe3O4 /Fe2O3 NANOCOMPOSITES BY SINTERING PROCESS - Muhammad Ghufron; Malik Anjelh Baqiya; Mashuri Mashuri; Triwikantoro Triwikantoro; Darminto Darminto (Jurnal Sains Materi Indonesia, 2011)
PHASE TRANSITION IN Fe3O4/Fe2O3 NANOCOMPOSITES BY SINTERING PROCESS. Fe3O4 powders have been successfully produced by using coprecipitation method. The characterization using X-Ray Diffraction method resulted in the size of Fe3O4 powders of 9.1 ± 0.3 nm. Samples were then formed into pellete and powders. Heat treatment at temperature 600 oC of powder samples for 1 hour and 2 hours give maghemite and hematite phases, but heat treatment at temperature 700-800 oC for 1 hour, 2 hours and 3 hours give only one phase namely hematite. Heat treatment at temperature 600 oC, 700 oC and 800 oC of pelletes for 1 hour, 2 hours and 3 hours give also only one phase which is hematite. Quantitative analysis using MAUD program resulted in Fe3O4/Fe2O3 composites with changing crystal size at increasing temperature.